2016
DOI: 10.1111/cmi.12552
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration and metabolism of host cell arginine by the intraerythrocytic malaria parasitePlasmodium falciparum

Abstract: Human erythrocytes have an active nitric oxide synthase, which converts arginine into citrulline and nitric oxide (NO). NO serves several important functions, including the maintenance of normal erythrocyte deformability, thereby ensuring efficient passage of the red blood cell through narrow microcapillaries. Here, we show that following invasion by the malaria parasite Plasmodium falciparum the arginine pool in the host erythrocyte compartment is sequestered and metabolized by the parasite. Arginine from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…However, the protein has not been subject to detailed study and its function is not previously established. Function could not be detected following heterologous expression in Xenopus laevis oocytes 29 , in contrast to the yeast expression system described here. Reasons for this difference may include differences in protein folding or localization in the two expression systems.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, the protein has not been subject to detailed study and its function is not previously established. Function could not be detected following heterologous expression in Xenopus laevis oocytes 29 , in contrast to the yeast expression system described here. Reasons for this difference may include differences in protein folding or localization in the two expression systems.…”
Section: Discussioncontrasting
confidence: 81%
“…It transpires that this homologue is a putative amino acid transporter in which SNPs were previously linked to chloroquine resistance in malaria parasites 27 , 28 . A recent attempt at characterisation by heterologous expression in Xenopus laevis oocytes did not produce detectably-functional protein 29 . Here we successfully apply a yeast heterologous expression system to show that the parasite protein mediates uptake of quinoline drugs so altering the level of drug resistance.…”
Section: Introductionmentioning
confidence: 97%
“…The functional characteristics of Pb NPT1 expressed in Xenopus oocytes are very similar to those of the pathway mediating the uptake of arginine into P. falciparum parasites 31 , consistent with the P. falciparum orthologue of Pb NPT1 (PF3D7_0104800) serving as the major arginine transporter in asexual-stage P. falciparum parasites. P. falciparum infection causes depletion of arginine in the host erythrocyte 31 , and Plasmodium infection leads to hypoargininaemia, a depletion of arginine in the plasma of the host that contributes to poor disease outcomes such as cerebral malaria 33 34 . Plasmodium NPT1 conceivably plays a role in Plasmodium -induced hypoargininaemia.…”
Section: Resultssupporting
confidence: 63%
“…Intraerythrocytic asexual stages of the human malaria parasite P. falciparum have been shown to take up exogenous arginine via an unidentified pathway that is inhibited by other cationic amino acids 31 32 . The functional characteristics of Pb NPT1 expressed in Xenopus oocytes are very similar to those of the pathway mediating the uptake of arginine into P. falciparum parasites 31 , consistent with the P. falciparum orthologue of Pb NPT1 (PF3D7_0104800) serving as the major arginine transporter in asexual-stage P. falciparum parasites. P. falciparum infection causes depletion of arginine in the host erythrocyte 31 , and Plasmodium infection leads to hypoargininaemia, a depletion of arginine in the plasma of the host that contributes to poor disease outcomes such as cerebral malaria 33 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has further been shown that, following erythrocyte invasion by P . falciparum , the Arg pool in the host compartment is sequestered and metabolized by the parasite into citrulline and ornithine 41 . Of note, polyamines have been shown to be among the major metabolites present within blood-stage P .…”
Section: Discussionmentioning
confidence: 99%